Rural Areas in Bulgaria – Investigation on some Factors for Development - Yarkova, Yuliana; Mutafov, Emil (Eastern European Countryside, 2024)
The focus on the specific territories such as rural areas as systems is imperative in order to achieve each of the strategic goals of development at national and European level. The objective of current paper is a subject to the project “7I/14 Regional policy against depopulation of Bulgarian villages” which aims to bring to light opportunities and fields of interventions to reduce depopulation of Bulgarian villages and to formulate recommendations and measures at national and regional level. Present study limits its tasks to: systematization and classification of the factors for development of the rural areas, investigation the role of institutional actors and pointing out the factors that constraint the successful development and some pathways of resolving the bottlenecks. Since the objective data show significant disparities between developed and underdeveloped rural regions and specificity of development factors, a subjective empirical study (survey) among 144 respondents from two regions – underdeveloped and developed, has been conducted. The object of this paper is the discussion on just two of all 13 questions in the questionnaire: 1) the role of the institutions and organizations for the future development of rural areas and 2) the factors limiting development of rural areas.